HUBUNGAN KOMORBID DENGAN KEPARAHAN COVID-19 DI RUMAH SAKIT DARURAT COVID-19 WISMA ATLET KEMAYORAN JAKARTA PUSAT TAHUN 2022 - Eke Mahendra; Ramadhan Tosepu; Asriati Asriati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
challenge worldwide in the health sector related to the ongoing spread of the virus. More cases of death occur in the elderly and have co-morbidities. The purpose of this study was to analyze the relationship between comorbidities and COVID-19 severity at the Wisma Atlet Kemayoran Central Jakarta COVID-19 emergency hospital in 2022. The type of research was a survey with a cross-sectional study design. The study population was patients who were confirmed positive for COVID-19 with symptoms at the Wisma Atlet Kemayoran Emergency Hospital from July to December 2021. The study sample was 400 people. The results showed that the 6 variables studied, 4 variables that had a correlation with the severity of Covid-19 patients, namely hypertension from Sig. (2-tailed) 0.000, cardiovascular obtained Sig. (2-tailed) = 0.000, tuberculosis obtained Sig. (2-tailed) = 0.000 and comorbidities obtained Sig. (2-tailed) = 0.000. Meanwhile, diabetes mellitus and asthma do not have a correlation relationship with the severity level in Covid patients who obtained a Sig value. (2-tailed) respectively, namely = 0.483 and 0.599